A Survey on Nepali Migrants in India: An Empirical Study (The Geographic Base, 2020)
This article examines the status of Nepali migrants in Delhi-NCR, India. Due to open border, shorter distance and long-established social network, migration from Nepal to India has been unending. India has been an origin and destination country for large numbers of migrants. A treaty in 1950, between Nepal and India facilitates movement between Nepal and India. This paper analyzed the nature and pattern of migrants’ employment, education, social network, and causes of migration. Nevertheless, the improved income level, the condition of most of the migrant workers is deplorable, most of them are staying together in either poor rented houses or at slums with sharing rooms without proper provision of hygienic sanitation. Social networks are the major entry point for getting jobs, shelter and loans and for saving money. Nepali migrants in Delhi are working for basic survival rather than improvement in their living standards.